5th International Scientific Conference: Is it Time for a Total Reset? (University of Maribor Press, 2021)
The Proceedings of 5th International Scientific Conference organized by University of Maribor, Faculty of Economics and Business entitled »Is It Time for a Total Reset?« comprises four sections. Economics is covered by convergence trends in human development indicators in EU, characteristics of savings in North Macedonia, response of households to Covid-19 epidemic and its effect on food and beverages industry. The second part is devoted to management and it presents a case study of market entry of emerging small enterprises, circular economy in case of secondary use of raw materials in Poland, a simplification of administrative procedures in Italy, and most common approaches to motivating employees in public administration. The digitalization section includes general presentations of digitalization and its challenges in marketing and education. The fourth part displays effects of Covid-19 epidemic to legal order, to teaching business English and to EU strategy for growth, competitiveness and sustainable development.